Modeling principles of protective thyroid blocking. (4th May 2022) - Rump, Alexis; Eder, Stefan; Hermann, Cornelius; Lamkowski, Andreas; Kinoshita, Manabu; Yamamoto, Tetsuo; Take, Junya; Abend, Michael; Shinomiya, Nariyoshi; Port, Matthias
Abstract: Purpose: In the case of a nuclear incident, the release of radioiodine must be expected. Radioiodine accumulates in the thyroid and by irradiation enhances the risk of cancer. Large doses of stable (non-radioactive) iodine may inhibit radioiodine accumulation and protect the thyroid ('thyroid blocking'). Protection is based on a competition at the active carrier site in the cellular membrane and an additional temporary inhibition of the organification of iodide (Wolff-Chaikoff effect). Alternatively, other agents like e.g. perchlorate that compete with iodide for the uptake into the thyrocytes may also confer thyroidal protection against radioiodine exposure. Biokinetic models for radioiodine mostly describe exchanges between compartments by first order kinetics. This leads to correct predictions only for low (radio)iodide concentrations. These models are not suited to describe the kinetics of iodine if administered at the dosages recommended for thyroid blocking and moreover does not permit to simulate either the protective competition mechanism at the membrane or the Wolff-Chaikoff effect. Models adapted for this purpose must be used. Such models may use a mathematical relation between the serum iodide concentration and a relative uptake suppression or a dependent rate constant determining total thyroidal radioiodine accumulation. Alternatively, the thyroidal uptake rate constant may be modeled as a function of the total iodine content of the gland relative to a saturation amount. Newer models integrate a carrier-mechanism described by Michalis-Menten kinetics in the membrane and in analogy to enzyme kinetics apply the rate law for monomolecular irreversible enzyme reactions with competing substrates to model the competition mechanism. An additional total iodide uptake block, independent on competition but limited in time, is used to simulate the Wolff-Chaikoff effect. Conclusion: The selection of the best model depends on the issue to be studied. Most models cannot quantify the relative contributions of the competition mechanism at the membrane and the Wolff-Chaikoff effect. This makes it impossible or exceedingly difficult to simulate prolonged radioiodine exposure and the effect of repetitive administrations of stable iodine. The newer thyroid blocking models with a separate modeling of competition and Wolff-Chaikoff effect allow better quantitative mechanistic insights and offer the possibility to simulate complex radioiodine exposure scenarios and various protective dosage schemes of stable iodine relatively easily. Moreover, they permit to study the protective effects of other competitors at the membrane carrier site, like e.g. perchlorate, and to draw conclusions on their protective efficacy in comparison to stable iodine.